A preparation process of ABS composite material
By mixing ABS, polytetrafluoroethylene powder, polyvinyl chloride and phenyl polyguanidine phosphate intermediates in a high-speed disperser, extruded and granulated in a twin-screw extruder, and finally molding with an injection molding machine, ABS composite materials with good flame retardant and antibacterial properties were prepared, which solved the problems of the existing ABS materials being fast burned and lacking antibacterial properties.
Patent Information
- Application Number
- CN202410790212.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-06-19
AI Technical Summary
The existing ABS materials are faster when burning and lack antibacterial properties, which limits their application areas.
By mixing ABS, polytetrafluoroethylene powder, polyvinyl chloride and phenyl polyguanidine phosphate intermediates evenly in a high-speed disperser, extruded and granulated in a twin-screw extruder, and finally molded using an injection molding machine, ABS composite materials with good flame retardant and antibacterial properties were prepared.
The prepared ABS composite material not only has good flame retardant properties, but can effectively inhibit combustion, and significantly improve antibacterial properties through the electrostatic adsorption of doguanidine groups.
Smart Images

Figure CN118546492B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ABS materials, and in particular to a preparation process of an ABS composite material. Background Art
[0002] Acrylonitrile-butadiene-styrene (ABS) copolymer is a thermoplastic polymer material with high strength, good toughness and easy processing and molding. It is widely used in home appliances, toys, machinery, automobiles, instruments and other fields. However, pure ABS products burn quickly and produce a large number of molten droplets. Therefore, it needs to be flame-retardant modified to improve the application field of ABS.
[0003] Polyvinyl chloride is a synthetic polymer plastic with good flame retardancy, chemical resistance and other properties. Polytetrafluoroethylene powder has good heat resistance, weather resistance, flame retardancy, self-lubricating properties and other properties.
[0004] For example, the patent with application publication number CN103509313A discloses a toughened foam material of recycled ABS and a preparation method thereof. The invention uses ABS, polyvinyl chloride, flame retardant and other raw materials to prepare an ABS material with good flame retardant properties, but does not improve the antibacterial properties of ABS. Summary of the invention
[0005] 1. Technical issues to be solved
[0006] In view of the deficiencies of the prior art, the present invention provides a process for preparing an ABS material composite material. The ABS composite material prepared by the present invention has good antibacterial and flame retardant properties.
[0007] (II) Technical solution
[0008] A preparation process of an ABS composite material, the preparation process comprising:
[0009] Add dried ABS, polytetrafluoroethylene powder, polyvinyl chloride, and polyguanidine phenyl phosphate intermediate into a high-speed disperser, stir and mix evenly, and then place in a twin-screw extruder for extrusion granulation. After pelletizing, dry at 80-100° C. for 2-5 hours. After drying, use an injection molding machine for injection molding to obtain an ABS composite material.
[0010] Furthermore, the mass ratio of the ABS, polytetrafluoroethylene powder, polyvinyl chloride, and polyguanidine phenyl phosphate intermediate is 100:10-20:40-70:5-15.
[0011] Furthermore, the processing temperature when using the twin-screw extruder is 180-220° C., and the screw speed is 320-380 r / min.
[0012] Furthermore, the injection molding temperature is 200-240° C., and the injection molding pressure is 100-130 MPa.
[0013] Furthermore, the preparation process of the polyguanidine phenyl phosphate intermediate is:
[0014] (1) Add 3,5-diaminobenzonitrile to deionized water, stir and disperse, then add 30-40% hydrochloric acid and dicyandiamide, stir and disperse, heat to 80-90° C., react for 5-12 hours, and after the reaction is completed, concentrate under reduced pressure, precipitate with acetone, filter, wash with deionized water, and dry to obtain intermediate 1.
[0015] (2) Intermediate 1, BF 3 -Et 2 O、NaBH 4 Add to tetrahydrofuran solvent, stir and disperse, react at 60-70°C for 12-24h. After the reaction is completed, cool to room temperature, evaporate by rotary evaporation, add deionized water, stir, extract with dichloromethane, and evaporate by rotary evaporation to obtain intermediate 2.
[0016] (3) Add intermediate 2 to tetrahydrofuran solvent, stir and disperse, then add phenyl dichloride phosphate and triethylamine, react at 40-50° C. for 5-10 hours, and after the reaction is completed, filter, wash with ethanol, and dry to obtain a polyguanidine phenyl phosphate intermediate.
[0017] Furthermore, in the step (1), the molar ratio of 3,5-diaminobenzonitrile to dicyandiamide is 1:4-6.
[0018] Furthermore, in the step (2), intermediate 1, BF 3 -Et 2 O、NaBH 4 The molar ratio is 1:1.8-2.5:2-3.
[0019] Furthermore, in the step (3), the molar ratio of the intermediate 2, phenyl dichloride phosphate and triethylamine is 2-2.8:1:3.5-5.
[0020] (III) Beneficial technical effects
[0021] The present invention uses 3,5-diaminobenzonitrile, dicyandiamide, dichlorophenyl phosphate and the like as raw materials, and prepares a polyguanidine phenyl phosphate intermediate through addition reaction, reduction reaction and substitution reaction. Finally, polytetrafluoroethylene powder, polyvinyl chloride and the polyguanidine phenyl phosphate intermediate are added to ABS, mixed evenly, extruded and granulated, and injection molded to obtain an ABS composite material. The polytetrafluoroethylene powder used in the present invention has good self-lubricity, forms a transfer film during friction, and can increase the wear resistance of the ABS composite material.
[0022] The ABS composite material prepared by the present invention contains more phosphorus and nitrogen elements. The phosphorus element contained therein generates strong dehydrating substances such as phosphoric acid and metaphosphoric acid when heated, which promotes the dehydration of the material into carbon, forms a dense carbon layer on the surface of the material, isolates the material transportation and energy transfer, and hinders the combustion of the material. The nitrogen element contained therein generates more flame-retardant gas when heated, dilutes the content of flammable gas in the air, and further hinders the combustion of the material.
[0023] The ABS composite material prepared by the present invention contains more guanidine groups, which can be adsorbed on the surface of negatively charged microorganisms through electrostatic action, thereby hindering the action of cell lysozyme, causing the cell surface structure to deform and destroy, thereby inhibiting the reproduction of bacteria and achieving a good antibacterial effect. The polyguanidine phenyl phosphate intermediate prepared by the present invention has a simple preparation method and a novel structure, and the polyguanidine groups contained therein have better antibacterial properties than monoguanidine groups. The ABS composite material prepared by the present invention has a good antibacterial effect and a flame retardant effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a preparation route for polyguanidine phenyl phosphate intermediates. DETAILED DESCRIPTION
[0025] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are provided. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0026] Example 1
[0027] (1) Add 20 mmol of 3,5-diaminobenzonitrile to deionized water, stir and disperse, then add 38% hydrochloric acid and 120 mmol of dicyandiamide, stir and disperse, heat to 85°C, react for 6 hours, and after the reaction is completed, concentrate under reduced pressure, precipitate with acetone, filter, wash with deionized water, and dry to obtain intermediate 1.
[0028] (2) 1 mol of intermediate 1 and 2.2 mol of BF 3 -Et 2 O, 2.5 mol NaBH 4 Add to tetrahydrofuran solvent, stir and disperse, react at 65°C for 24 hours. After the reaction is completed, cool to room temperature, evaporate by rotary evaporation, add deionized water, stir, extract with dichloromethane, and evaporate by rotary evaporation to obtain intermediate 2.
[0029] (3) Add 24 mmol of intermediate 2 to tetrahydrofuran solvent, stir and disperse, then add 10 mmol of phenyl dichloride phosphate and 50 mmol of triethylamine, react at 50° C. for 8 h. After the reaction is completed, filter, wash with ethanol, and dry to obtain a polyguanidine phenyl phosphate intermediate.
[0030] (4) Add 20 g of dried ABS, 2 g of polytetrafluoroethylene powder, 10 g of polyvinyl chloride, and 1 g of polyguanidine phenyl phosphate intermediate into a high-speed disperser, stir and mix evenly, and then place in a twin-screw extruder for extrusion granulation, wherein the temperature is 220° C. and the screw speed is 350 r / min. After pelletizing, dry at 90° C. for 5 h. After drying, use an injection molding machine for injection molding, wherein the injection molding temperature is 240° C. and the injection molding pressure is 100 MPa to obtain an ABS composite material.
[0031] Example 2
[0032] (1) Add 20 mmol of 3,5-diaminobenzonitrile to deionized water, stir and disperse, then add 40% hydrochloric acid and 90 mmol of dicyandiamide, stir and disperse, heat to 90°C, react for 12 hours, and after the reaction is completed, concentrate under reduced pressure, precipitate with acetone, filter, wash with deionized water, and dry to obtain intermediate 1.
[0033] (2) 1 mol of intermediate 1 and 2 mol of BF 3 -Et 2 O, 2.5 mol NaBH 4 Add to tetrahydrofuran solvent, stir and disperse, react at 65°C for 20 hours. After the reaction is completed, cool to room temperature, evaporate by rotary evaporation, add deionized water, stir, extract with dichloromethane, and evaporate by rotary evaporation to obtain intermediate 2.
[0034] (3) Add 25 mmol of intermediate 2 to tetrahydrofuran solvent, stir and disperse, then add 10 mmol of dichlorophenyl phosphate and 40 mmol of triethylamine, react at 50° C. for 6 h. After the reaction is completed, filter, wash with ethanol, and dry to obtain a polyguanidine phenyl phosphate intermediate.
[0035] (4) Add 20 g of dried ABS, 2.5 g of polytetrafluoroethylene powder, 14 g of polyvinyl chloride, and 1.5 g of polyguanidine phenyl phosphate intermediate into a high-speed disperser, stir and mix evenly, and then place in a twin-screw extruder for extrusion granulation, wherein the temperature is 180° C. and the screw speed is 380 r / min. After pelletizing, dry at 80° C. for 5 h. After drying, use an injection molding machine for injection molding, wherein the injection molding temperature is 220° C. and the injection molding pressure is 110 MPa to obtain an ABS composite material.
[0036] Example 3
[0037] (1) Add 20 mmol of 3,5-diaminobenzonitrile to deionized water, stir and disperse, then add 30% hydrochloric acid and 80 mmol of dicyandiamide, stir and disperse, heat to 80°C, react for 5 hours, and then concentrate under reduced pressure, precipitate with acetone, filter, wash with deionized water, and dry to obtain intermediate 1.
[0038] (2) 1 mol of intermediate 1 and 2.5 mol of BF 3 -Et 2 O, 2.5 mol NaBH 4 Add to tetrahydrofuran solvent, stir and disperse, react at 70°C for 20 hours. After the reaction is completed, cool to room temperature, evaporate by rotary evaporation, add deionized water, stir, extract with dichloromethane, and evaporate by rotary evaporation to obtain intermediate 2.
[0039] (3) Add 25 mmol of intermediate 2 to tetrahydrofuran solvent, stir and disperse, then add 10 mmol of dichlorophenyl phosphate and 35 mmol of triethylamine, react at 40° C. for 6 h. After the reaction is completed, filter, wash with ethanol, and dry to obtain a polyguanidine phenyl phosphate intermediate.
[0040] (4) Add 20 g of dried ABS, 3 g of polytetrafluoroethylene powder, 8 g of polyvinyl chloride, and 2 g of polyguanidine phenyl phosphate intermediate into a high-speed disperser, stir and mix evenly, and then place in a twin-screw extruder for extrusion granulation, wherein the temperature is 200° C. and the screw speed is 320 r / min. After pelletizing, dry at 100° C. for 2 h. After drying, use an injection molding machine for injection molding, wherein the injection molding temperature is 200° C. and the injection molding pressure is 130 MPa to obtain an ABS composite material.
[0041] Example 4
[0042] (1) Add 20 mmol of 3,5-diaminobenzonitrile to deionized water, stir and disperse, then add 35% hydrochloric acid and 85 mmol of dicyandiamide, stir and disperse, heat to 85° C., react for 10 h, and after the reaction is completed, concentrate under reduced pressure, precipitate with acetone, filter, wash with deionized water, and dry to obtain intermediate 1.
[0043] (2) 1 mol of intermediate 1 and 2 mol of BF 3 -Et 2 O, 3 mol NaBH 4 Add to tetrahydrofuran solvent, stir and disperse, react at 60°C for 12 hours. After the reaction is completed, cool to room temperature, evaporate by rotary evaporation, add deionized water, stir, extract with dichloromethane, and evaporate by rotary evaporation to obtain intermediate 2.
[0044] (3) Add 20 mmol of intermediate 2 to tetrahydrofuran solvent, stir and disperse, then add 10 mmol of dichlorophenyl phosphate and 50 mmol of triethylamine, react at 50° C. for 5 h. After the reaction is completed, filter, wash with ethanol, and dry to obtain a polyguanidine phenyl phosphate intermediate.
[0045] (4) Add 20 g of dried ABS, 3 g of polytetrafluoroethylene powder, 12 g of polyvinyl chloride, and 2.5 g of polyguanidine phenyl phosphate intermediate into a high-speed disperser, stir and mix evenly, and then place in a twin-screw extruder for extrusion granulation, wherein the temperature is 190° C. and the screw speed is 340 r / min. After pelletizing, dry at 90° C. for 4 h. After drying, use an injection molding machine for injection molding, wherein the injection molding temperature is 220° C. and the injection molding pressure is 120 MPa to obtain an ABS composite material.
[0046] Example 5
[0047] (1) Add 20 mmol of 3,5-diaminobenzonitrile to deionized water, stir and disperse, then add 38% hydrochloric acid and 120 mmol of dicyandiamide, stir and disperse, heat to 85° C., react for 6 h, and after the reaction is completed, concentrate under reduced pressure, precipitate with acetone, filter, wash with deionized water, and dry to obtain intermediate 1.
[0048] (2) 1 mol of intermediate 1 and 1.8 mol of BF 3 -Et 2 O, 2 mol NaBH 4 Add to tetrahydrofuran solvent, stir and disperse, react at 65°C for 24 hours. After the reaction is completed, cool to room temperature, evaporate by rotary evaporation, add deionized water, stir, extract with dichloromethane, and evaporate by rotary evaporation to obtain intermediate 2.
[0049] (3) Add 28 mmol of intermediate 2 to tetrahydrofuran solvent, stir and disperse, then add 10 mmol of dichlorophenyl phosphate and 40 mmol of triethylamine, react at 45° C. for 10 h. After the reaction is completed, filter, wash with ethanol, and dry to obtain a polyguanidine phenyl phosphate intermediate.
[0050] (4) Add 20 g of dried ABS, 4 g of polytetrafluoroethylene powder, 12 g of polyvinyl chloride, and 3 g of polyguanidine phenyl phosphate intermediate into a high-speed disperser, stir and mix evenly, and then place in a twin-screw extruder for extrusion granulation, wherein the temperature is 210° C. and the screw speed is 360 r / min. After pelletizing, dry at 90° C. for 4 h. After drying, use an injection molding machine for injection molding, wherein the injection molding temperature is 240° C. and the injection molding pressure is 100 MPa to obtain an ABS composite material.
[0051] Comparative Example 1
[0052] The difference between this comparative example and the embodiment is that in step (4), no polyguanidinophenyl phosphate intermediate is contained.
[0053] The flame retardant properties of ABS composite materials were tested using a horizontal vertical combustion apparatus.
[0054] Use an oxygen index tester to test the flame retardant properties of ABS composite materials.
[0055] Table 1: Flame retardant performance test results of various embodiments and comparative examples
[0056] LOI / % Vertical burning level Example 1 27.5 V-1 Example 2 29.8 V-0 Example 3 30.2 V-0 Example 4 31.8 V-0 Example 5 32.1 V-0 Comparative Example 1 22.2 V-2
[0057] It can be seen from the table that the ABS composite material prepared by the present invention has good flame retardant properties.
[0058] According to GB / T31402-2015, the test bacteria is Staphylococcus aureus, R=(U t -U 0 )-(A t -U 0 )=U t -A t , U 0 It is the logarithmic average of the number of bacteria immediately after inoculation of the sample without antibacterial treatment, CFU / cm 2 ; U t It is the logarithmic mean of the number of bacteria in the sample without antibacterial treatment 24 hours after inoculation, CFU / cm 2 ; A t It is the logarithmic mean of the number of bacteria in the antibacterial treated sample 24 hours after inoculation, CFU / cm 2 .
[0059] Table 2: Antibacterial performance test results of various embodiments and comparative examples
[0060]
[0061]
[0062] It can be seen from the table that the ABS composite material prepared by the present invention has good antibacterial properties.
[0063] The notched impact performance of ABS composite materials was tested using a simply supported beam impact tester.
[0064] Use a universal electronic tensile testing machine to test the tensile properties of ABS composite materials.
[0065] Table 3: Mechanical properties test results of various embodiments and comparative examples
[0066]
[0067] It can be seen from the table that the ABS composite material prepared by the present invention has good mechanical properties.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A process for preparing an ABS composite material, characterized in that: The preparation process is: Add dried ABS, polytetrafluoroethylene powder, polyvinyl chloride, and polyguanidine phenyl phosphate intermediate into a high-speed disperser, stir and mix evenly, and then place in a twin-screw extruder for extrusion granulation. After pelletizing, dry at 80-100° C. for 2-5 hours. After drying, use an injection molding machine for injection molding to obtain an ABS composite material. The preparation process of the polyguanidine phenyl phosphate intermediate is as follows: (1) Add 3,5-diaminobenzonitrile to deionized water, stir and disperse, then add 30-40% hydrochloric acid and dicyandiamide, stir and disperse, heat to 80-90°C, react for 5-12 hours, and after the reaction is completed, concentrate under reduced pressure, precipitate with acetone, filter, wash with deionized water, and dry to obtain intermediate 1; (2) Add intermediate 1, BF3-Et2O and NaBH4 to tetrahydrofuran solvent, stir and disperse, react at 60-70°C for 12-24 hours, cool to room temperature after the reaction, perform rotary evaporation, add deionized water, stir, extract with dichloromethane, and perform rotary evaporation to obtain intermediate 2; (3) Add intermediate 2 to tetrahydrofuran solvent, stir and disperse, then add phenyl dichloride phosphate and triethylamine, react at 40-50°C for 5-10 hours. After the reaction is completed, filter, wash with ethanol, and dry to obtain a polyguanidine phenyl phosphate intermediate.
2. The preparation process of the ABS composite material according to claim 1, characterized in that: The mass ratio of the ABS, polytetrafluoroethylene powder, polyvinyl chloride and polyguanidine phenyl phosphate intermediate is 100:10-20:40-70:5-15.
3. The preparation process of the ABS composite material according to claim 1, characterized in that: The processing temperature of the twin-screw extruder is 180-220° C., and the screw speed is 320-380 r / min.
4. The preparation process of the ABS composite material according to claim 1, characterized in that: The injection molding temperature is 200-240° C., and the injection molding pressure is 100-130 MPa.
5. The preparation process of the ABS composite material according to claim 1, characterized in that: In the step (1), the molar ratio of 3,5-diaminobenzonitrile to dicyandiamide is 1:4-6.
6. The preparation process of the ABS composite material according to claim 1, characterized in that: In the step (2), the molar ratio of intermediate 1, BF3-Et2O and NaBH4 is 1:1.8-2.5:2-3.
7. The process for preparing the ABS composite material according to claim 1, characterized in that: In the step (3), the molar ratio of the intermediate 2, phenyl dichloride phosphate and triethylamine is 2-2.8:1:3.5-5.
Citation Information
Patent Citations
Recycled-ABS toughened foam material and preparation method thereof
CN103509313A
Preparation method and application of phenyl phosphorus nitrogen diphosphonate synergistic flame retardant containing cyclotriphosphazene
CN106995535A
Flame-retardant heat-resistant ABS plastic particle
CN113604002A